2022
DOI: 10.1002/cplu.202100518
|View full text |Cite
|
Sign up to set email alerts
|

Deciphering the Role of Noncovalent Interactions in the Conformations of Dibenzo‐1,5‐dichalcogenocines

Abstract: This work reports a combined experimental and theoretical study on the new dibenzo‐1,5‐ditellurocine 2‐Te in order to get an overview on the parameters controlling conformational change and to explain the differences with sulfur and selenium analogues. The preference of the boat conformer over the chair one is revealed by DFT calculations. For 2‐Te, a ΔG value of about 3 kJ/mol was calculated, close to the value measured by NMR (5 kJ/mol). However, DFT calculations with implicit solvation effects could not cle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 98 publications
0
17
0
Order By: Relevance
“…As we recently demonstrated that chlorinated solvents clearly interact in solution with Te σ‐holes, [12] we performed similar experiments with less competitive solvents than CDCl 3 , i. e. toluene‐ d8 and cyclohexane‐ d12 . In order to increase the strength of the Te⋅⋅⋅O interaction, a stronger σ‐hole acceptor (Et 3 PO [36] ) was also used.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…As we recently demonstrated that chlorinated solvents clearly interact in solution with Te σ‐holes, [12] we performed similar experiments with less competitive solvents than CDCl 3 , i. e. toluene‐ d8 and cyclohexane‐ d12 . In order to increase the strength of the Te⋅⋅⋅O interaction, a stronger σ‐hole acceptor (Et 3 PO [36] ) was also used.…”
Section: Resultsmentioning
confidence: 96%
“…Based on such considerations, we are thus conducting detailed investigations of selected organotellurium compounds in order to tune σ‐hole deepness and look at the resulting interactions, [12] in the solid state but mostly in solution, with the aim to apply them to catalysis [11e] . For the present study, we selected diaryl ditellurides where each tellurium atom possesses two σ‐holes at the antipode of C−Te (σ Te‐C ) and Te−Te (σ Te‐Te ) bonds (Figure 1B).…”
Section: Introductionmentioning
confidence: 99%
“…As we recently demonstrated that chlorinated solvents clearly interact in solution with Te holes, [12] we performed similar experiments with less competitive solvents than CDCl3, i.e. toluene-d8 and cyclohexane-d12.…”
Section: Resultsmentioning
confidence: 99%
“…Based on such considerations, we are thus conducting detailed investigations of selected organotellurium compounds in order to tune -hole deepness and look at the resulting interactions [12] , in the solid state but mostly in solution, with the aim to apply them to catalysis. [11e] For the present study, we selected diaryl ditellurides where each tellurium atom possesses two -holes at the antipode of C-Te (Te-C) and Te-Te (Te-Te) bonds (Figure 1B).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, Weiss et al observed that the boat conformer of dibenzo-1,5-ditellurocine is more stable than the chair conformer. Their analysis reveals the presence of an interaction between Te and C-H. 26 It is noteworthy that although there are reports on H-bonds involving heavier chalcogen atoms, polonium still remains unexplored. Polonium is a naturally occurring radioactive element, and not many molecules containing polonium are known.…”
Section: Introductionmentioning
confidence: 99%